The internal and external determinants that affect the profitability performance of Bank Islam Malaysia Berhad / Mohd Zafran Mohd Salleh - Mohd Salleh, Mohd Zafran (Faculty of Business and Management, 2017)
This study is conducted to determine the internal and external factors that affect the profitability performance of Bank Islam Malaysia Berhad (BIMB) that cover thirty years period starting in year 1986 until 2015. The data has been analyzed to determine the internal and external factors that affect profitability of BIMB. Meanwhile, to identify the factors of its profitability, the Least Square Method has been used. All the data had been obtained from secondary sources through published journal, books, working papers, BIMB annual bank report and etc. Malaysia has been proved to be at the forefront of Islamic banking and finance in the world wide. Islamic banking is gaining popularity among non-Muslim across the globe due to its wider product and services. Hence, this study is carried out to identify the internal and external factors that affect the profitability performance of BIMB. Based on the findings, Gross Domestic Product (GDP) and Total Equity to Total Asset (TETA) are positively significant and affect the BIMB’s profitability. Meanwhile the other determinants such fuel price (OIL) and Total Deposit to Total Asset (TDTA) are not significant to BIMB’s profitability.